Diseño e implementación de un sistema automatizado con paneles solares para obtener energía redundante de dc/ac en la agrícola “Lucila” del recinto tres coronas del cantón La Maná, año 2013 - Sinchiguano Vega, Wellington Paúl (2015)
This research project aims to fulfil the economic feasibility for the commercialization of solar panels in Ecuador. Global warming has undoubtedly contributed to the undertaking of business related to the distribution of electricity through renewable methods. Ecuador is a dependent and a poor culture of energy saving country, the lack of large hydroelectric power stations which has caused discontent in society. Particularly in times of rationing, for which it has created the need to find alternatives that benefit the community.